Find the value of the following (using an epsilon proof or basic limit properties (no L'hospital)):

$$\lim_{x\to\infty}\left( \sqrt{(x+a)(x+b)}-x \right)\forall a,b\in\mathbb{R}$$

I've tried rewriting it in several ways, but I don't seem to bet getting very far; I always end up with something in indeterminate form. How can you prove the value of this? Any hints?

  • 2
    $\begingroup$ Hint: $$\sqrt{(x+a)(x+b)}=\sqrt{x^2+(a+b)x+ab}=\sqrt{\left(x+\frac{a+b}2\right)^2+ab-\frac{(a+b)^2}4}$$ $\endgroup$ – Prasun Biswas Apr 12 '18 at 1:09

\begin{align*} \lim_{x\to\infty}\left( \sqrt{(x+a)(x+b)}-x \right)&=\lim_{x\to\infty}\frac{(x+a)(x+b)-x^2}{ \sqrt{(x+a)(x+b)}+x }\\ &=\lim_{x\to\infty}\frac{(a+b)x+ab}{ \sqrt{(x+a)(x+b)}+x }\\ &=\lim_{x\to\infty}\frac{(a+b)+\frac{ab}{x}}{ \sqrt{(1+\frac{a}{x})(1+\frac{b}{x})}+1 }\\ &=\frac{a+b}{2} \end{align*}


HINT: First divide and multiply by $\sqrt{(x+a)(x+b)}+x$.


Hint: $$\sqrt{(x+a)(x+b)}=\sqrt{x^2+(a+b)x+ab}=\sqrt{\left(x+\frac{a+b}2\right)^2+ab-\frac{(a+b)^2}4}$$


Can you generalize this for $n$ constants $a_1,a_2,\ldots,a_n$ with the surd being $\sqrt[n]{\cdot}$ ?

Hint for the generalization:


What is the coefficient of $x^{n-1}$ in $\prod\limits_1^n (x-a_i)$ scaled by $1/n$ ?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.